Repetitive and Prolonged Omega-3 Fatty Acid Treatment after Traumatic Brain Injury Enhances Long-Term Tissue Restoration and Cognitive Recovery. Issue 4 (April 2017) - Pu, Hongjian; Jiang, Xiaoyan; Wei, Zhishuo; Hong, Dandan; Hassan, Sulaiman; Zhang, Wenting; Liu, Jialin; Meng, Hengxing; Shi, Yejie; Chen, Ling; Chen, Jun
Traumatic brain injury (TBI) is one of the most disabling clinical conditions that could lead to neurocognitive disorders in survivors. Our group and others previously reported that prophylactic enrichment of dietary omega-3 polyunsaturated fatty acids (n-3 PUFAs) markedly ameliorate cognitive deficits after TBI. However, it remains unclear whether a clinically relevant therapeutic regimen with n-3 PUFAs administered after TBI would still offer significant improvement of long-term cognitive recovery. In the present study, we employed the decline of spatial cognitive function as a main outcome after TBI to investigate the therapeutic efficacy of post-TBI n-3 PUFA treatment and the underlying mechanisms. Mice were subjected to sham operation or controlled cortical impact, followed by random assignment to receive the following four treatments: (1) vehicle control; (2) daily intraperitoneal injections of n-3 PUFAs for 2 weeks, beginning 2 h after TBI; (3) fish oil dietary supplementation throughout the study, beginning 1 day after TBI; or (4) combination of treatments (2) and (3). Spatial cognitive deficits and chronic brain tissue loss, as well as endogenous brain repair processes such as neurogenesis, angiogenesis, and oligodendrogenesis, were evaluated up to 35 days after TBI. The results revealed prominent spatial cognitive deficits and massive tissue loss caused by TBI. Among all mice receiving post-TBI n-3 PUFA treatments, the combined treatment of fish oil dietary supplement and n-3 PUFA injections demonstrated a reproducible beneficial effect in attenuating cognitive deficits although without reducing gross tissue loss. Mechanistically, the combined treatment promoted post-TBI restorative processes in the brain, including generation of immature neurons, microvessels, and oligodendrocytes, each of which was significantly correlated with the improved cognitive recovery. These results indicated that repetitive and prolonged n-3 PUFA treatments after TBI are capable of enhancing brain remodeling and could be developed as a potential therapy to treat TBI victims in the clinic.